(untitled) (Itinera, 2024)
Le Rouge et le Noir is taken as an example of a novel in which the hero, and some other characters, experience strong tension between inner consciousness and social habits. Stendhal’s novel is a particularly significant example because it is shaped by the immediate afterlife of the French Revolution and the writings of Rousseau. The revolutionary rupture with habit intersects with the themes of a consciousness looking for inner existence and the role of inner passions. The Revolution was an exception, prolonged by the rise of Bonaparte which appeals to a hero frustrated by the habitual conformity of anti-revolutionary France after the fall of Bonaparte. He seeks a great career, and he seeks grandeur in love, always combining passions with strategy in an unstable mix. He moves from love with a comparative innocent to love with a woman who shares his obsessions though they have different objects. The final crisis of the novel leads to a breakdown of the hero’s habitual self, in an ending in which passions becomes both destructive violence and an idyllic solitary resignation. The journey into an interiority, through exceptional breaks with habit finds a culmination. This achievement rests on Stendhal writing in a world after Rousseau and understanding the full extent of this requires a rounded understanding of Rousseau, along with his context.